2022
DOI: 10.3389/fruro.2022.904452
|View full text |Cite
|
Sign up to set email alerts
|

Posterior urethral valve in children: Using novel biomarkers as an early predictive tool for the onset and progression of chronic kidney disease

Abstract: This narrative review aims to appraise the current evidence on using biomarkers of obstructive nephropathy to predict the onset and progression of chronic kidney disease (CKD) in infants with posterior urethral valves (PUV). PUV is the most frequently reported congenital anomaly of the kidney and urinary tract (CAKUT) associated with bladder outlet obstruction in male children. It contributes significantly to the CKD burden in childhood. Despite different approaches for its postnatal repair, evidence-based dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…In the absence of any tubular dysfunction, notwithstanding anything that filters across is catabolized by the proximal tubules and does not appear in urine. It is only when there is a proximal tubular malfunction, the uCysC will rise[ 15 , 34 , 35 ] It is expected that the uncatabolized uCysC in a similar concentration might not reach the urinary bladder due to an obstruction present at the ureteropelvic junction Thus, this hypothesis explains the reason for similar levels of uCysC observed between the cases and controls by Madsen et al . [ 11 ] and Karakus et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of any tubular dysfunction, notwithstanding anything that filters across is catabolized by the proximal tubules and does not appear in urine. It is only when there is a proximal tubular malfunction, the uCysC will rise[ 15 , 34 , 35 ] It is expected that the uncatabolized uCysC in a similar concentration might not reach the urinary bladder due to an obstruction present at the ureteropelvic junction Thus, this hypothesis explains the reason for similar levels of uCysC observed between the cases and controls by Madsen et al . [ 11 ] and Karakus et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] found a significantly higher mean uCysC in patients with renal tubular diseases (4.13 ± 3.85 mg/l) than that of the controls (0.096 ± 0.044 mg/l), whereas Uwaezuoke et al . [ 35 ] suggested that a higher the serum CysC will be observed in patients with glomerular diseases [ Figure 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the very limited published data available on the pattern and pathways of RPN in African population, the hallmark of the disease depends on geographical location, environmental hazards and the quality of basic health care system [7][8][9]. The most morbid risk factors are unknown and underdiagnosed genetic diseases such as congenital obstructive nephropathy (posterior urethral valves) [10], and sickle cell nephropathy [11]. The primary defect of sickle cell disease results from the replacement of glutamate for valine at the sixth amino acid of the beta globin chain.…”
Section: Introductionmentioning
confidence: 99%